Nutrition: What Factors Affect Outcomes? - Ahmed, Akhter; Hossain, Nusrat (2018)
Using two survey rounds of IFPRI's Bangladesh Integrated Household Survey (BIHS), IFPRI researchers from the Bangladesh Policy Research and Strategy Support Program (PRSSP) analyze factors that affect nutrition outcomes in the country, as well as offer policy considerations.